Friends in love ([s.l.] Viva Films, 1999)
They are four young people discovering love only for the first time. In the quiet, idyllic confines of their boarding school, their relationships bloom, but not for long. The day comes when they discover that they are mismatched, and that compatibility, more than affection, is what's needed to keep them going.
VCD
Sharon Cuneta, Jackie Lou Blanco, Rowell Santiago, William Martinez
Keywords: Feature films